Pithekoussan amphorae and the development of a Mediterranean market economy - Donnellan, Lieve (Journal of Greek Archaeology, 2020)
Growth has been the key word of recent ancient Mediterranean economic history, especially, but not exclusively, among scholars who operate within a New Institutional Economic (NIE) theoretical framework. The rising number of shipwrecks from around 900 BC to ca. 100 CE in the Mediterranean is seen as clear sign of a rapidly expanding and increasingly integrated economic system, encompassing the entire Mediterranean and eventually linking it with regions as far as the Arabian peninsula, India and China.